2015
DOI: 10.1142/s0217595915500074
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Analytic Network Process and Monte Carlo Analysis in New Product Formula Selection Decisions

Abstract: One crucial matter in routine life is decision-making. Although decision-making in everyday life appears to be easily dealt with by one-on-one comparisons, the same is not true with decision-making in business. In business management decisions, problems are more complicated than those in individual life because most business situations fall into the category of multi-criteria decision-making (MCDM) problems. Therefore, appropriate multi-criteria decision methods should be carefully selected to solve these prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Zha et al employed the ANP and TOPSIS method to rank the optimal facility layout alternatives, and compared the difference between ANP-TOPSIS and AHP-TOPSIS [39]. Wudhikarn et al improved the ANP method with Monte Carlo analysis and applied it in the new product formula selection decision [40]. Wang et al used the entropy weight and VIKOR methods to evaluate and optimize the design schemes [41].…”
Section: Mcdm and Its Application In Risk Management And Green Productmentioning
confidence: 99%
“…Zha et al employed the ANP and TOPSIS method to rank the optimal facility layout alternatives, and compared the difference between ANP-TOPSIS and AHP-TOPSIS [39]. Wudhikarn et al improved the ANP method with Monte Carlo analysis and applied it in the new product formula selection decision [40]. Wang et al used the entropy weight and VIKOR methods to evaluate and optimize the design schemes [41].…”
Section: Mcdm and Its Application In Risk Management And Green Productmentioning
confidence: 99%
“…Multi-Criteria Decision-Making (MCDM) techniques are often adopted to solve complex problems based on experts' judgment. Previous studies have shown that MCDM methods, combined with a fuzzy set theory or other methods [35,36], can result in more reliable results. Several studies have used this approach in the areas of health [37], safety [38] and environment [39], and economy [40] for identifying and classifying relationships among variables.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…(2) Comparison of weight determination methods The analytic network process method is widely used for MCDM [42,43], but the calculation process is complicated. To compensate for the shortcomings of this single method, hybrid evaluation methods with ANP [44,45] were proposed.…”
Section: ) Comparison Of Evaluation Criteriamentioning
confidence: 99%